Teacher Feedback And Students’ Participation in Classroom Interaction - Arsita Wulan Cahyani; Ivorie Rahiema Verandra Asyigah; Ruqoyyah Amilia Andania (Journal of English Language Teaching and Islamic Integration, 2024)
This study aims to explore the teacher feedback that use to promote classroom interaction. A descriptive qualitative research approach was utilized, incorporating observations, interviews, and questionnaires for data collection. The participants in this study two English teachers of senior high school.  The result revealed that the EFL teacher generally employs evaluative feedback to acknowledge and encourage students, making it the most common sort of verbal feedback in the transcript. This technique  promotes  a  positive  learning  environment  and  encourages  students  to participate in the session actively. To improve the learning experience, teachers should balance  the  use  of  evaluative,  interactive,  and  corrective  feedback.  Increasing interactive feedback by asking open-ended questions and promoting student discussion might help students grasp more deeply. More detailed corrective feedback, as well as opportunities  for  self-  and  peer-correction,  can  increase  learners'  awareness  and accountability.  Regular  evaluation  of feedback  practices,  as  well  as  incorporating student feedback, helps ensure that the methods utilized fit the different requirements of students.